Meaningful Work and Disability: A Dignity Towards Social Inclusion - Rosdianti, Yeni (Indonesian Journal of Disability Studies, 2017)
Access to employment is essential for every persons including persons with disabilities. If a meaningful work is enormously important, how does an equality framework advance this in securing access to the labour market? This paper will examine the way in which work is significant for persons with disabilities as a pathway towards social inclusion. It is apparantly drawn from the concept of dignity, equality and human rights. Accordingly, a substantive equality approach provides a powerful endowment to the fulfilment of the right to work of persons with disability.